Persistent antiferromagnetic order in heavily overdoped Ca1−xLaxFeAs2. (3rd September 2019) - Martino, Edoardo; Bachmann, Maja D; Rossi, Lidia; Modic, Kimberly A; Zivkovic, Ivica; Rønnow, Henrik M; Moll, Philip J W; Akrap, Ana; Forró, László; Katrych, Sergiy
Abstract: In the Ca1− x La x FeAs2 (1 1 2) family of pnictide superconductors, we have investigated a highly overdoped composition ( x   =  0.56), prepared by a high-pressure, high-temperature synthesis. Magnetic measurements show an antiferromagnetic transition at T N   =  120 K, well above the one at lower doping (0.15  <   x   <  0.27). Below the onset of long-range magnetic order at T N, the electrical resistivity is strongly reduced and is dominated by electron–electron interactions, as evident from its temperature dependence. The Seebeck coefficient shows a clear metallic behavior as in narrow band conductors. The temperature dependence of the Hall coefficient and the violation of Kohler's rule agree with the multiband character of the material. No superconductivity was observed down to 1.8 K. The success of the high-pressure synthesis encourages further investigations of the so far only partially explored phase diagram in this family of Iron-based high temperature superconductors.